Rational schemes of control of aviation fuel quality in the places of its consumption - Кулишенко, В. М.; Лахин, Б. Ф.; Малов, Б. А. (Proceedings of National Aviation University (archive), 1999)
Considered is aviation fuel quality corresponding to normatives of standard. Determined are the optimal correlation between the expenditure and the results of the analysis of fuel quality control